2019
DOI: 10.1021/acs.jpclett.9b00896
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Cubic FAPbI3 from X-ray Diffraction, Anelastic, and Dielectric Measurements

Abstract: Among the hybrid metal-organic perovskites for photovoltaic applications FAPbI 3 (FAPI) has the best performance regarding efficiency and the worst regarding stability, even though the reports on its stability are highly contradictory. In particular, since at room temperature the cubic α phase, black and with high photovoltaic efficiency, is metastable against the yellow hexagonal δ phase, it is believed that α−FAPI spontaneously transform into δ−FAPI within a relatively short time. We performed X-ray diffract… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
84
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(87 citation statements)
references
References 40 publications
3
84
0
Order By: Relevance
“…The yellow (δ) phase is nominally the most stable phase at room temperature, although the black (α) phase can be prepared during the synthesis and effectively quenched to room temperature. The δ phase can also be converted to the α phase on heating with the transition having been previously reported to be at 125°C, 22,29 however, this transition has been found to take place as low as 77°C 30 and up to 185°C, 31 which has been attributed to kinetics of the technique in use and the selected synthesis ramp rate, 32 respectively. A wide variation also exists for the duration of the black phase stability, once formed, ranging from a matter of hours 23,33,34 up to days, 24,[35][36][37][38] with the synthesis approach and the added nanoengineering templating 37,38 appearing to have an effect on stabilization.…”
Section: Introductionmentioning
confidence: 99%
“…The yellow (δ) phase is nominally the most stable phase at room temperature, although the black (α) phase can be prepared during the synthesis and effectively quenched to room temperature. The δ phase can also be converted to the α phase on heating with the transition having been previously reported to be at 125°C, 22,29 however, this transition has been found to take place as low as 77°C 30 and up to 185°C, 31 which has been attributed to kinetics of the technique in use and the selected synthesis ramp rate, 32 respectively. A wide variation also exists for the duration of the black phase stability, once formed, ranging from a matter of hours 23,33,34 up to days, 24,[35][36][37][38] with the synthesis approach and the added nanoengineering templating 37,38 appearing to have an effect on stabilization.…”
Section: Introductionmentioning
confidence: 99%
“…Also FAPbI 3 gives better stability than MAPbI 3 at high temperatures. [8][9][10] However, its major aw is that the black cubic a phase, which is responsible for the high photovoltaic efficiency, is metastable toward heat and moisture at normal operating conditions. [11][12][13] The stable phase, which is produced when FAPbI 3 is obtained by standard chemical methods, is the yellow hexagonal d phase.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, however, Cordero et al found that a-FAPbI 3 can be perfectly stable for at least 100 days unless extrinsic factors induce its degradation. 8 There have been extensive theoretical works studying the structure and electronic, optical, and defect properties of MAPbI 3 , and these have greatly deepened the understanding of MAPbI 3 and accelerated research into its application to devices. [14][15][16][17][18][19] Although there have been some of theoretical works studying FAPbI 3 , 20-24 a systematic and comprehensive study is still absent.…”
Section: Introductionmentioning
confidence: 99%
“…The intense peaks located at ≈14 o and ≈28 o are corresponding to (001) and (002) planes, respectively. [ 44,45 ] The XRD patterns shown in Figure 4e are measured with the optimal concentration of each additive as shown in Figure S2, Supporting Information, where the single MACl and CsCl additive is found to show best performance at 20 and 10 mol%, respectively, while 15 mol% shows best PCE for the [MACl]/[CsCl] = 2 additive among the investigated concentrations. It is found that the (001) peaks shift to higher angles as compared to the additive‐free perovskite sample, indicative of contraction of c‐axis due to substitution of FA with smaller ions.…”
Section: Resultsmentioning
confidence: 99%